Erratum to: Averaging Generalized Scalar Field Cosmologies Ii: Locally Rotationally Symmetric Bianchi I and Flat Friedmann–Lemaître–Robertson–Walker Models (the European Physical Journal C, 2021 81 6 489 10.1140/Epjc/S10052-021-09230-5) - Gonzalez-Banda, E (Springer Science and Business Media Deutschland GmbH, 2021)
In this article the following acknowledgment was replaced: This research was funded by Agencia Nacional de Investigación y Desarrollo-ANID through the program FONDECYT Iniciación grant no. 11180126 and by Vicerrectoría de Investigación y Desarrollo Tecnológico at Universidad Católica del Norte. Ellen de los Milagros Fernández Flores is acknowledged for proofreading this manuscript and improving the English. We thank anonymous referee for his/her comments which have helped us improve our work. © 2021, The Author(s).